Public and Private Secondary Education in Developing Countries : A Comparative Study. World Bank Discussion Papers No. 309 - Jimenez, Emmanuel; Lockheed, Marlaine E.; World Bank, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
This monograph summarizes the results of a World Bank research project that compared private and public secondary school costs and achievement in five developing countries--Columbia, the Dominican Republic, the Philippines, Tanzania, and Thailand. All the case studies address the question: Would a high school student, selected at random from the general student population, perform better in a public or private school? In the absence of experimental data, the studies compare students' performance on standardized tests in a cross-section of public and private schools. Student background, motivation, innate ability, and prior performance are controlled through the use of various statistical techniques. The report also compares the costs of public and private schools. The principal findings include: (1) although students in private schools come from more privileged families than those in public schools, on average, there is a significant overlap between the two groups; (2) with student background and selection bias held constant, students in private schools out-perform students in public schools on a variety of achievement tests; (3) unit costs of private schools are lower than those of public schools; and (4) private schools are organized for greater school-level decision making and emphasis on enhancing student achievement; this seems to affect the mix of inputs that private versus public schools choose. Implications for policy include: (1) over-restrictive regulations on private schools may be suppressing an efficient way to provide education; (2) in some cases, governments could encourage greater private sector participation in education; and (3) public schools could emulate at least some of the teaching and administrative practices of their private counterparts. Contains numerous tables throughout the document and 66 references. (EH)
Availability: The World Bank, 1818 H Street, N.W., Washington, DC 20433.
ERIC Note: Other contributors were Donald Cox, Eduardo Luna, Vicente Paqueo, M. L. de Vera, and Nongnuch Wattanawaha.
Keywords: Academic Achievement; Comparative Education; Cross Cultural Studies; Developing Nations; Development; Foreign Countries; Global Education; Private Schools; Public Schools; Secondary Education; Social Science Research; Colombia -- Dominican Republic -- Philippines -- Tanzania -- Thailand; Information Analyses; Reports, Research